Conserving land for people: transformative adaptive co-management of sustainable protected areas in the eastern Democratic Republic of Congo - Kalyongo, Kujirakwinja Deo (Rhodes University, Faculty of Science, Department of Environmental Science, 2020)
Conservation practices and approaches in the Democratic Republic of Congo (DRC), as in other parts of the world, have evolved from traditional to fortress and collaborative contemporary approaches such as adaptive co-management. These approaches aim to include multiple decision-makers using diversified resources and, existing formal and informal governance structures. Collaborative approaches also consider conflict resolution and external factors that can influence conservation outputs and outcomes. In the DRC context, conflicts over resources are related not only to resource access and power but also to the ineffectiveness of collaborative approaches that exclude stakeholders such as local communities. These conflicts have negatively affected protected areas and weakened the management and governance of protected areas. Therefore, evolving approaches such as adaptive co-management that consider power relations, the multi-scaled involvement of actors and learning loops to adjust strategies are seen as better options to improve the governance of protected areas and minimise the degradation of key ecosystems. My research explored the gazettement processes of three protected areas in the eastern DRC (Itombwe, Kabobo and Okapi Reserves). I focused on the influence of social-political, historical and psychological factors on the management and governance of protected areas in the DRC. In addition, the research reveals the inclusive gazettement processes of protected areas is the foundation of successful co-management approaches. I found that values and good governance practices play a key role in influencing local perceptions and support to conservation interventions. Whilst some conservation practitioners believe that economic benefits to communities are the most predominant motivating factor, I found that good conservation management practices can motivate communities to support protected area management. Bad management practices were related not only to inadequate conservation approaches and practices but also to factors such as corruption, inadequate law enforcement and the inappropriate equipment of rangers. Therefore, I suggest that long term protected area management in DRC should consider how the value of resources for communities and protected areas have been changing throughout the history of conservation, and how to best share power and responsibilities with local resource users and stakeholders. This is only possible if conservation practices and approaches, governance process and institutions are transformed at multiple levels.
Keywords: Protected areas -- Congo (Democratic Republic); Protected areas -- Government policy -- Congo (Democratic Republic); Protected areas -- Management -- Congo (Democratic Republic); Conservation of natural resources -- Congo (Democratic Republic)